Older patients affected by COVID-19: investigating the existence of biological phenotypes - Alberto Zucchelli; Marta Parigi; Silvia Giliani; Davide Liborio Vetrano; Daniela Lucente; Emanuele Marzetti; Riccardo Calvani; Giuseppe Bellelli; Alessandra Marengoni (BMC Geriatrics)
Abstract Introduction COVID-19 provides an opportunity to examine biological phenotypes (observable morphological, functional and biological characteristics) in individuals who experience the same acute condition, potentially revealing differences in response to acute external stressors. The aim our study was to investigate biological phenotypes in older patients hospitalized for COVID-19, exploiting a panel of aging biomarkers. Methods Data were gathered from the FRACOVID Project, an observational multicenter study, aimed to evaluate the impact of frailty on health-related outcomes in patients 60 + with COVID-19 in Northern Italy. A hierarchical cluster analysis was run using log-transformed and scaled values of TNF-a, IL-1 beta, IL-6, PAI-1, GDF-15, NT-proBNP, and Cystatin C evaluated at admission. Results Eighty-one participants (mean age 75.3 years; 60.5% male) were evaluated. Frailty was identified in 42% of the sample and 27.2% were unable to ambulate outdoors. The mean hospital stay was 24.7 days, with an in-hospital mortality rate of 18.5%. Three biological phenotypes were found: (1) ‘inflammatory’, with high inflammatory biomarkers; (2) ‘organ dysfunction’, characterized by elevated cystatin C and NT-proBNP, and lower inflammatory markers; and (3) ‘unspecific’, with lower NT-proBNP and GDF-15 levels, and intermediate concentrations of other biomarkers. The ’organ dysfunction’ phenotype showed the highest mean age and prevalence of frailty, disability, and chronic diseases. The ‘inflammatory‘ phenotype showed the highest burden of respiratory and systemic signs and symptoms of infection. Conclusion Biological phenotypes might be used to identify different clinical and functional phenotypes in individuals affected by COVID-19.